Official Selection at the 16th International Film Festival of Larissa - Thessaly, Greece - Margaritis, Charalambos (My University, 2026)
Official Selection of the film "74" at the 16th International Film Festival of Larissa - Thessaly, Greece.
Keywords: Arts and entertainment